Pengaruh Capital Expenditure, Risiko Keuangan dan Pertumbuhan Penjualan terhadap Nilai Perusahaan - Nurlatifah, Nurlatifah; Purwatiningsih, Purwatiningsih (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This study aims to analyze the effect of capital expenditure, financial risk and sales growth on company value in energy companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. This study uses a purposive sampling method with a population of 76 companies and 8 energy companies were obtained as samples with an observation period of 5 years. The data used in this study are secondary data obtained from www.idx.co.id and from the websites of each company. The data analysis method used is quantitative data using panel data regression analysis using the E-views 12 tool. This study shows that Capital Expenditure, Financial Risk and Sales Growth have a simultaneous effect on Company Value. The results of this study indicate that Capital Expenditure partially does not affect company value, but Financial Risk and Sales Growth partially affect company value.